Mixed Co-Mn oxide-catalysed selective aerobic oxidation of vanillyl alcohol to vanillin in base-free conditions - Jha, Ajay; Patil, Kashinath R.; Rode, Chandrashekhar V. (Chempluschem, 2013)
Manganese-doped cobalt mixed oxide (MnCo-MO) catalyst was prepared by a solvothermal method. The as-prepared catalyst was characterised by X-ray photoelectron spectroscopy, H-2 temperature-programmed reduction, O-2 temperature-programmed oxidation and XRD. This catalyst gave 62% conversion with 83% selectivity to vanillin in 2hours for the liquid-phase air oxidation of vanillyl alcohol without using base. Three different types of metal oxides were observed in the prepared catalyst, which could be identified as Co3O4, Mn3O4 and CoMn2O4. Among these, the tetragonal phase of CoMn2O4 was found to be more active and selective for vanillyl alcohol oxidation than Co3O4 and Mn3O4. High-resolution TEM characterisation revealed the morphology of MnCo-MO nanorods with a particle size of 10nm. Successful recycling of the catalyst was also established in this oxidation reaction.
Keywords: aerobic oxidation; cobalt; heterogeneous catalysis; manganese; spinel phases

Method to form semiconductor quantum dot (QD) thin films by igniting a flame at air-liquid interface: CdS and WO3 - Jadhav, Aarti H.; Patil, Sagar H.; Sathaye, Shivaram D.; Patil, Kashinath R. (Journal of Colloid and Interface Science, 2015)
We reveal an easy, inexpensive, efficient one step flame synthesis of semiconductor/metal oxide thin films at air-liquid interface, subsequently, transferred on suitable substrate. The method has been illustrated by the formation of CdS and Wo(3) QDs thin films. The features of the present method are (1) Growth of thin films consisting of 0.5-2.0 nm sized Quantum Dots (QDs)/(ultra-small nanoparticles) in a short time, at the air-liquid interface which can be suitably transferred by a well-known Blodgett technique to an appropriate substrate, (2) The method is suitable to apply layer by layer (LbL) technique to increase the film thickness as well as forming various compositions as revealed by AFM measurements. The films are characterized for their structure (SAED), morphology (TEM), optical properties (UV-Vis.) and photoluminescence (PL). Possible mechanism of formation of QDs thin film and effect of capping in case of COS QDs is discussed. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: CdS; Flame synthesis; interface; Quantum Dots (QDs); thin film; WO3

Multifunctional polyaniline-tin oxide (PANI-SnO2) nanocomposite: synthesis, electrochemical, and field emission investigations - Patil, Sandip S.; Harpale, Kashmira V.; Koiry, Shankar P.; Patil, Kashinath R.; Aswal, Dinesh K.; More, Mahendra A. (Journal of Applied Polymer Science, 2015)
Synthesis of PANI-SnO2 nanocomposite has been performed using a simple two step chemical oxidative polymerization route. The structural, morphological and chemical properties of the as-synthesized PANI-SnO2 nanocomposite have been revealed by various characterization techniques such as SEM, TEM, XRD, FTIR, and XPS. Interestingly the as-synthesized PANI-SnO2 nanocomposite exhibits supercapacitance value of 721 F g(-1) with energy density 64 Wh kg(-1), which is noticed to be higher than that of pristine SnO2 and PANI nanostructures. Furthermore, the galvanostatic charge-discharge characteristics revealed pseudocapacitive nature of the PANI-SnO2 nanocomposite. The estimated values of charge transfer resistance and series resistance estimated from the Nyquist plot are found to be lower. Along with the supercapacitive nature, PANI-SnO2 nanocomposite showed promising field emission behavior. The threshold field, required to draw emission current density of 1 A/cm(2), is observed to be 0.90 V/m and emission current density of 1.2 mA/cm(2) has been drawn at applied field of approximate to 2.6 V/m. The emission current stability investigated at preset values of 0.02 and 0.1 mA/cm(2) is observed to be fairly stable over duration of more than 3 h. The enhanced supercapacitance values, as well as, the promising field emission characteristics are attributed to the synergic effect of SnO2 nanoparticles and PANI nanotubes. (c) 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41401.
Keywords: conducting polymers; Electrochemistry; nanostructured polymers; surfaces and interfaces

Methanol oxidation reaction on Pt based electrocatalysts modified ultramicroelectrode (UME): Novel electrochemical method for monitoring rate of CO adsorption - Joshi, Vrushali S.; Poudyal, Durgasha C.; Satpati, Ashis K.; Patil, Kashinath R.; Haram, Santosh K. (Electrochimica Acta, 2018)
Novel fast scan cyclic voltammetry (FSCV) based method has been developed to study methanol oxidation reaction on Pt nanoparticles (PtNPs) based catalysts. To support the cyclic voltammetry measurements at higher scan rates, micron-sized electrode geometries viz. PtNPs loaded on the single strand of carbon fiber (SSCF) and PtNPs decorated multiwalled carbon nanotubes (MWCNTs), loaded on commercial ultramicroelectrode (UME) have been employed. Deconvolution of the voltammograms obtained during methanol oxidation revealed three major anodic peaks. These peaks have been plausibly attributed to the electron transfer processes viz. methanol oxidation into CO/other intermediates, oxidation of these intermediates into CO2 and adsorption of un-oxidized CO on the catalyst surface. The peaks due to CO adsorption have been elucidated as a function of scan rates. The area under the peak as a function of time has been correlated to the rate of CO adsorption on these catalysts. The average rate of CO adsorption in methanol oxidation at Pt-SSCF and Pt-MWCNTs/UME are estimated to be 1.08 x 10(-8) mol cm(-2) s(-1) and 13.5 x 10(-8) mol cm(-2) s(-1) respectively. This novel method is proposed to generalize to any electrocatalysts of interest. (C) 2018 Published by Elsevier Ltd.